Towards a Post-Neoliberal Social Policy? Social Investment versus Capability Approach - Laruffa, Francesco (Momentum Quarterly, 2018)
Despite remaining dominant, neo-liberalism increasingly lacks popular support. This offers the opportunity to develop progressive alternatives to neo-liberalism. In the academic debate on social policy, social investment has emerged as the normative paradigm for framing welfare reform after neo-liberalism. This paper assesses the validity of two claims: firstly, that social investment represents an alternative to neo-liberalism and secondly, that it involves a redefinition of social policy goals in line with Amartya Sen’s capability approach. Linking these two claims, the paper argues that while social investment differs from welfare retrenchment at the level of policy instruments, its alleged break with neo-liberalism is less clear-cut – particularly at the epistemological and normative level. Similarly, while social investment may resonate with the capability approach at the level of policy proposals, they differ in terms of normative principles and epistemological assumptions. These differences, in turn, have important implications for the formulation and implementation of social policy.